Effects of task-based approach on students' writing fluency and accuracy: A case in an upper secondary school - Hồng Thị Chiến (Trường Đại học Trà Vinh, 2021)
Students’writing drawbacks have become one of the most prominent issues in EFL writing classrooms and how to improve students writing skills is always a primary concern of most high school teachers of English.Therefore, the purpose of this study is to explore whether the Task-based approach enhance EFL students’writing performance in terms of fluency and accuracy.The participants are sixty grade eleven students of the two classes at Dai An High School, in Tra Vinh provine. Pre-test, post-test, questionaire and interview were used to measure the students’writing performance in term of writing fluency and accuracy. The study indicates that the experimental group attained the significant improvement in the post-test results due to the treatment of Task-based approach, which lasts for fourteen weeks. Additionally. The finding from questionaire and interview confirmed that the students expressed positive attitudes towards Task-based approach.The outcomes of the current study is the affirmation of a new and innovative teaching approach, new opportunities forstudents and a new role for the teachers.